Amitraz and Its Metabolites: Oxidative Stress-Mediated Cytotoxicity in HepG2 Cells and Study of Their Stability and Characterization in Honey - Marialuce Giorgini; Mercedes Taroncher; Josefa Tolosa; María-José Ruiz; Yelko Rodríguez-Carrasco (MDPI AG, 2023)
The population decrease of bees that has been observed in recent years due to the Varroa destructor parasite may endanger the production of bee-products whose demand is on the rise. To minimize the negative effects caused by this parasite, the pesticide amitraz is commonly used by beekeepers. Based on these, the objectives of this work are to determine the toxic effects caused by amitraz and its metabolites in HepG2 cells, as well as its determination in honey samples and the study of its stability with different heat treatments commonly used in the honey industry and its relationship with the amount of 5-hydroxymethylfurfural (HMF) produced. Amitraz significantly decreased cell viability by MTT assay and total protein content (PC) assay, being more cytotoxic than its metabolites. Amitraz and its metabolites caused oxidative stress by Lipid Peroxidation (LPO) production and Reactive Oxygen Species (ROS) generation. Residues of amitraz and/or its metabolites were found in analyzed honey samples, with 2,4-Dimethylaniline (2,4-DMA) being the main metabolite confirmed by high-performance liquid chromatography-high resolution mass spectrometry (HPLC-QTOF HRMS). Amitraz and its metabolites resulted as unstable even at moderate heat treatments. Additionally, a positive correlation in terms of HMF concentration in samples and the severity of heat treatment was also observed. However, quantified amitraz and HMF were within the levels set in the regulation.